2014
DOI: 10.5152/ucd.2014.2512
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of factors affecting mortality in Fournier’s Gangrene: Retrospective clinical study of sixteen cases

Abstract: Objective: Fournier's gangrene is a progressive, necrotizing fasciitis due to synergistic infection of the perineum and external genitalia that is associated with high mortality and morbidity. The purpose of this study is to review the diagnostic and treatment methods that effect mortality in Fournier's gangrene. Material and Methods:Sixteen patients who were diagnosed and treated at our clinic between 2011 and 2013 due to Fournier's gangrene were retrospectively analyzed. The surviving and non-surviving patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
21
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 8 publications
(4 reference statements)
0
21
1
2
Order By: Relevance
“…Many studies have shown that perianal infections are the most common etiological factor in Fournier's gangrene. [2,6,9,11,14] In our study, 52% of the patients had a perianal origin, and 16% had a urogenital origin; no clear etiology could be revealed in 32% of the patients due to the lack of records.…”
Section: Discussioncontrasting
confidence: 47%
See 4 more Smart Citations
“…Many studies have shown that perianal infections are the most common etiological factor in Fournier's gangrene. [2,6,9,11,14] In our study, 52% of the patients had a perianal origin, and 16% had a urogenital origin; no clear etiology could be revealed in 32% of the patients due to the lack of records.…”
Section: Discussioncontrasting
confidence: 47%
“…[5,6,9,13] The reason for its decreased prevalence in women is explained by the simpler drainage of the female perineum via the vaginal route. Furthermore, many reports on this condition have been published by urology clinics in which men predominated in samples, which led to males being over-represented in reports.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations